(untitled) (Docentes 2.0 Journal, 2021)
The research proposed is a sample of the breaking down of academic walls that lead students to investigate their neighboring communities. It was presented under a pedagogical practice of participatory communication within the classroom, which sought to strengthen the social fabric built from the bilateral academy-community approach, from an exercise of reconstruction of historical memory with the students of the 6th semester of Social Communication - Journalism from Uniminuto, Zipaquirá Regional Center. The initial purpose was debated in investigating identity reflections of unique conformation, with the popular stories of the older adult of the municipality. For this, an Action Research exercise was proposed, guided by semi-structured interviews, field diaries, and documentary research, which finally allowed them to recognize, reconstruct and strengthen their memory and identify the site. This strategy debated the pedagogical practices within the classroom thought outwards, creating, at the same time, spaces for academic analysis-reflection around the context. This leads to a deep approach to popular memory processes in the municipality of Zipaquirá, reevaluating the forms of identity rescue of oral tradition immersed in the territory. Likewise, the training of student researchers was proposed, capable of recognizing their reality, taking action, and alternating on it.